Pengaruh Modal Psikologi Terhadap Kinerja Pegawai Melalui Motivasi Kerja Pada Pegawai Pengemban Fungsi Keuangan Di Lingkungan Kepolisian Daerah Istimewa Yogyakarta - Andi Indro Pratomo; Agus Utomo (STIE AUB Surakarta, 2025)
The aim of the research is to determine, test and analyze empirically the significance of the influence of psychological capital on employee performance through work motivation in employees carrying out financial functions in the Yogyakarta Special Region Regional Police. The research uses a quantitative approach. Primary data from respondents, with data collection techniques namely questionnaires. The sample using census/population techniques was 30 employees. Data analysis using instrument tests, linearity, hypotheses, and mediation analysis with bootstrap process Hayes 4.0. The results of the t test prove that psychological capital has a significant effect on work motivation, psychological capital has a significant effect on performance, work motivation has an insignificant effect on performance. Work motivation as a mediator has a significant effect on the influence of psychological capital on performance. The results of the F test show that the variables psychological capital and work motivation have a significant effect on performance. The total R2 test result is 0.898. This means that performance is explained by psychological capital variables and work motivation variables amounting to 89.8% and the remaining 10.1% is explained by other variables outside this research model. Analysis of direct and indirect influence paths has proven that the direct influence of psychological capital on employee performance is an effective and dominant path.